Influência das frentes frias nos mecanismos de funcionamento da represa da UHE Carlos Botelho (Lobo/Broa) Itirapina SP, dos pontos de vista químico, físico e biológico - Passerini, Mariana Duó (Universidade Federal de São Carlos, 2010)
In Brazil there is a numerical predominance of river systems, which favors the construction of reservoirs. These reservoirs have great ecological, economic and social significance, so, the management, conservation and recovery of these systems are of fundamental importance with repercussions on the economy, social work and the uses of aquatic systems. Climatological phenomena, such as the passage of cold fronts, are important factors that influence the water quality of reservoirs. Given this, this work aimed to study the influence of cold fronts in the mechanisms of function of the hydroelectric reservoir of Carlos Botelho (Lobo/Broa), the change in the phytoplankton community, in the destratification of the water column and the change in chemical and physical composition of the reservoir, thus contributing to the understanding of the phenomenon of global circulation of aquatic systems, especially in shallow reservoirs. Two samples were collected for this work, one in the dry season and another in the wet season. The environmental variables were collected in the water column, resulting in the vertical profile of the reservoir. The results show that before the passage of the cold front, during periods of low wind speed, we could see the stratification formed in the water column. During the passage of the cold front, the stress of wind increase and the solar radiation decrease and temperature decreases, promoting vertical mixing of water, resulting in the destratified water column and thus providing homogeneity of physical and chemical variables and the resuspension of nutrients and diatoms that were dormant in the sediment and their rapid multiplication in the water column.
Keywords: Limnologia; Frentes frias; Fitoplâncton; Reservatórios de água; Nutrientes; Reservatórios; Reservoirs; Phytoplankton; Cold fronts; Nutrients; CIENCIAS BIOLOGICAS::ECOLOGIA